2007
DOI: 10.1002/elps.200600524
|View full text |Cite
|
Sign up to set email alerts
|

Development of an integrated approach for evaluation of 2‐D gel image analysis: Impact of multiple proteins in single spots on comparative proteomics in conventional 2‐D gel/MALDI workflow

Abstract: With 2-D gel mapping, it is often observed that essentially identical proteins migrate to different positions in the gel, while some seemingly well-resolved protein spots consist of multiple proteins. These observations can undermine the validity of gel-based comparative proteomic studies. Through a comparison of protein identifications using direct MALDI-TOF/ TOF and LC-ESI-MS/MS analyses of 2-D gel separated proteins from cauliflower florets, we have developed an integrated approach to improve the accuracy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 45 publications
1
69
0
Order By: Relevance
“…[34][35][36][37] As a result, the screening for disease markers became one of the main topics in a large number of proteomic studies in the past decade. [38][39][40][41][42] In this study, we performed a proteomic analysis to investigate tumor-specific protein expression of human breast carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] As a result, the screening for disease markers became one of the main topics in a large number of proteomic studies in the past decade. [38][39][40][41][42] In this study, we performed a proteomic analysis to investigate tumor-specific protein expression of human breast carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Bands spanning 63 kDa (about 4 mm) were excised and submitted for proteomic analysis (Cornell Proteomics Facility, Cornell University, Ithaca). The SDS-gel slices were subjected to in-gel digestion by trypsin and subsequent extraction (38). The digest was reconstituted in 10 l of 2% acetonitrile with 0.5% formic acid for nano-LC-ESI-MS/MS analysis using a UltiMate3000 nano-LC system coupled to a LTQ-Orbitrap Velos mass spectrometer (Thermo-Fisher Scientific, San Jose, CA) equipped with a "CorConneX" nano ion source device (CorSolutions LLC, Ithaca, NY).…”
Section: Methodsmentioning
confidence: 99%
“…Only scores for the peptides defined by Mascot probability analysis significantly greater than "identity" were considered for peptide identification. The exponentially modified protein abundance index (emPAI) number outputted directly from Mascot results for each identified proteins was used for estimation of relative protein amounts within the same gel bands (38).…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to minimize comigration of multiple protein species, we also used a relatively narrow pH range (4-7) for isoelectric focusing because the use of narrow-range immobilized pH gradient strips facilitates higher resolution (McGregor and Dunn, 2006;Sghaier-Hammami et al, 2009). However, MALDI-MS/MS is known to identify the most prevalent protein present in a gel spot sample (Jun et al, 2012), and the top-ranked hit resulting from LC-MS/MS analysis has also been shown typically to correspond to the most abundant protein among multiple proteins present in a spot (Yang et al, 2007). The spot intensities of different protein constituents were determined using the protein abundance index and the exponentially modified protein abundance index (emPAI; Supplemental Table S3), which have been routinely applied in proteomics workflows (Perkins et al, 1999;Ishihama et al, 2005;Zhang et al, 2006;Yang et al, 2007;Cilia et al, 2011;Taylor et al, 2011).…”
Section: Proteomic Changes In Low-oxalate Transgenic Fruitmentioning
confidence: 99%